Protection of best interest: a study on children working in entertainment industry in malaysia and their right to education - Nor Aida, Ab. Kadir; Naziree, Md Yusof; Maheran, Makhtar (2019)
In Malaysian, there is no law prohibits children to be working in the entertainment industry. However, the law merely provides minimal protection to those working in ‘public entertainment.’ Previous study showed that children in the entertainment business have been exposed to all types of abuse and neglects. It could be that the children suffer from health and psychological issue, physical harm or sexual abuse that may be caused by the working environment or the working conditions. The right to receive proper education may also be affected. In line with Article 3 of United Nations Convention on the Rights of Child 1989, this study suggest for entertainment industry to have a proper guidelines that serves as a child protection policy. It will discuss on the side effect of working in entertainment industry especially on the rights to education. First, it explains the right to education and describes the working conditions of children in the show business. Apart from that, it shows the impact of their work in entertainment business on the realisation of their right to education. The other focus of this study is the principles governing minors and their involvement in the entertainment industry and to identify significant problems in the protection of the right to education. This study shows that law and policy, as well as legal enforcement are needed to fully protect children from any risk and harm.